Suppression of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) After a Second Wave in Victoria, Australia. (23rd December 2020) - Giles, Michelle L; Wallace, Euan M; Alpren, Charles; Brady, Nicole; Crouch, Simon; Romanes, Finn; Sutton, Brett; Cheng, Allen
Abstract: Countries worldwide are experiencing a second wave of coronavirus disease 2019 (COVID-19), which is proving to be difficult to control. We describe the combination of physical distancing, mandatory mask wearing, movement restrictions, and enhanced test, trace, and isolation efforts that can be used to successfully suppress community transmission to zero.